MANAGERIAL COMPETENCY OF THE PRINCIPAL IN SMA BANUA KALIMANTAN SELATAN BILINGUAL BOARDING SCHOOL - Fitria Wulandari; Haris Fadillah; Ainur Rahman; Nur Azizah (MANAGERIA: Jurnal Manajemen Pendidikan Islam, 2022)
To improve the quality of human resources, the principal must manage human resources in schools. Well-organized resource management will achieve educational goals. Managerial competence is part of the principal's requirements that must be met. It is the principal capital in achieving the goals of education as a whole. This research is field research with a qualitative approach. The focus of this research is the managerial competence of the principal at the SPK (School of Cooperation Education) SMA Banua Kalsel Bilingual Boarding School in South Kalimantan. The results showed that the principal had managed human resources well. Schools can realize their vision and mission according to the objectives of the school initiated by the South Kalimantan government, namely the availability of excellent schools that can deliver outstanding students at national and international levels, and graduates can continue to the next level both at home and abroad.